2019
DOI: 10.1039/c9tc02842k
|View full text |Cite
|
Sign up to set email alerts
|

High unsaturated room-temperature magnetoresistance in phase-engineered MoxW1−xTe2+δultrathin films

Abstract: Ultrathin Td-Mo0.27W0.71Te2.02 films synthesized using a chemical vapor deposition method exhibit a non-saturating magnetoresistance of 11% at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…1 d). The results are in accordance with previous WAL data in these family of compounds 64 . The calculated α value − 0.449 confirms the WAL effect in the system.…”
Section: Resultssupporting
confidence: 93%
“…1 d). The results are in accordance with previous WAL data in these family of compounds 64 . The calculated α value − 0.449 confirms the WAL effect in the system.…”
Section: Resultssupporting
confidence: 93%
“…Recently, Chen et al reported the CVD growth of Mo x W 1−x Te 2 film with the assist of an hBN covered substrate, but probably due to the polycrystalline structure or substrate limit, no superconductivity or Weyl semimetal related properties were observed. 21 Therefore, obtaining high-quality atomic layers with controlled compositions of Mo x W 1−x Te 2 alloy on a normal silicon substrate remains challenging at present. In this work, we report a CVD method to synthesize Mo x W 1−x Te 2 alloy with different thicknesses and tunable stoichiometric ratios of cations Mo/W.…”
Section: Introductionmentioning
confidence: 99%
“…To further broaden the research potential of Mo x W 1– x Te 2 alloy, the chemical vapor deposition (CVD) method which is widely regarded as a facile technology in controllable synthesis and large-scale applications, appears to be a promising alternative for fast and scalable production of thickness-controlled Mo x W 1– x Te 2 alloy. Recently, Chen et al reported the CVD growth of Mo x W 1– x Te 2 film with the assist of an hBN covered substrate, but probably due to the polycrystalline structure or substrate limit, no superconductivity or Weyl semimetal related properties were observed . Therefore, obtaining high-quality atomic layers with controlled compositions of Mo x W 1– x Te 2 alloy on a normal silicon substrate remains challenging at present.…”
Section: Introductionmentioning
confidence: 99%
“…The following reaction mechanism is proposed to explain the formation of WTe 2 with the Te/W/NaCl mixed powder under the Ar/H 2 atmospheric pressure (Figure A). , …”
Section: Resultsmentioning
confidence: 99%